Namibia : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper assesses the impact of alternative fiscal consolidation strategies on Namibia's growth. It uses a model developed at the IMF to gain insights on what would be a growth-friendly composition of the fiscal adjustment. The analysis suggests that a combined strategy of revenue and expenditure measures has lower negative effects on growth than a pure expenditure-based adjustment. Structural reforms improving the efficiency of public investment can further reduce the negative effect of consolidation on growth, and potentially strengthen growth. Overall, minimizing the negative impact of fiscal consolidation on growth requires combining revenue and expenditure measures, together with fiscal structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet